Navigating nephrology: unveiling pharmacist perspectives on renal dose adjustment in Saudi Arabia – a comprehensive cross-sectional analysis - Hind M. Alosaimi; Rshed A. Alwatban; Haifa M. Alshammari; Ahmed H. Alshammari; Shatha S. Alanazi; Meshal A. Alreshidi; Abeer A. Alreshidi; Abrar S. Alsayed; Furat A. Alfaraj; Kawther A. Alzayer; Aymen A. Alzaher; Khawla M. Almutairi; et al. (Journal of Pharmaceutical Policy and Practice, 2024)
ABSTRACTIntroduction Chronic kidney disease (CKD) is a major public health concern in Saudi Arabia. it is pertinent to mention that in the Southwestern region of Saudi Arabia. Hypertension and diabetes mellites are considered the major drivers of CKD. Research has documented worldwide the inappropriate dose adjustments in patients, ranging from 25% to 77%, of drugs requiring dose modifications. Pharmacists are pivotal members of the healthcare team, tasked with addressing issues pertaining to medications. This study aims to unveil pharmacist perspectives on renal dose adjustment in Saudi Arabia an important step in gauging their involvement in promoting healthy behaviours.Method A cross-sectional study design was conducted from December 2023 to January 2024 among pharmacists working in diverse healthcare settings, including clinical and hospital pharmacies, retail, and community pharmacies who had direct encounters with patients diagnosed with CKD. A validated questionnaire, the Renal Dose Adjustment-13 (RDQ-13) was used for this study. For comparing the knowledge, attitude, and perception scores of pharmacists statistical tests like One-Way ANOVA, and independent t-test; while for factors influencing the knowledge, attitude, and perception scores a multivariate linear regression was performed. The statistical significance level was set at 0.05.Results A total of 379 pharmacists completed the questionnaire, the knowledge score of pharmacists was 22.06 ± 2.81, while the attitude score was 8.56 ± 2.62 and the practice score was 5.75 ± 2.25. The findings of multivariate linear regression analysis indicated a statistically significant positive association between knowledge score and pharmacist’s age while for practice score the findings revealed a statistically negative association between working setting and designation of pharmacists.Conclusion The pharmacist in Saudi Arabia exhibited a proficient knowledge score of drug dosage adjustment pertinent to renal function while the attitude and practice score was less as compared to the knowledge score.